Smoke-Free Rules and Secondhand Smoke Exposure in Homes and Vehicles Among US Adults, 2009–2010 - King, Brian A. (Centers for Disease Control and Prevention, 2013)
INTRODUCTION: An increasing number of US states and localities have implemented comprehensive policies prohibiting tobacco smoking in all indoor areas of public places and worksites. However, private settings such as homes and vehicles remain a major source of exposure to secondhand smoke (SHS) for many people. This study assessed the prevalence and correlates of voluntary smoke-free rules and SHS exposure in homes and vehicles among US adults. METHODS: We obtained data from the 2009–2010 National Adult Tobacco Survey, a landline and cellular-telephone survey of adults aged 18 years or older residing in the 50 US states or the District of Columbia. We calculated national and state estimates of smoke-free rules and past-7-day SHS exposure in homes and vehicles and examined national estimates by sex, age, race/ethnicity, and education. RESULTS: The national prevalence of voluntary smoke-free home rules was 81.1% (state range, 67.9%–92.9%), and the prevalence of household smoke-free vehicle rules was 73.6% (state range, 58.6%–85.8%). Among nonsmokers, the prevalence of SHS exposure was 6.0% in homes (state range, 2.4%–13.0%) and 9.2% in vehicles (state range, 4.8%–13.7%). SHS exposure among nonsmokers was greatest among men, younger adults, non-Hispanic blacks, and those with a lower level of education. CONCLUSION: Most US adults report having voluntary smoke-free home and vehicle rules; however, millions of people remain exposed to SHS in these environments. Disparities in exposure also exist among certain states and subpopulations. Efforts are needed to warn about the dangers of SHS and to promote voluntary smoke-free home and vehicle rules.